Dialog Interreligious Representasi dari Transformasi Pendidikan Toleransi - Muthoharoh (Penamas, 2023)
Interreligious dialogue on Habib Husein Ja'far Al-Hadar's YouTube channel, which continuously voices tolerance through interreligious dialogue. Habib Ja'far is a content creator whose content contains da'wah and education packaged in such a way that it is easily accepted by all groups, both the old and the young. This research aims to investigate the values of tolerance contained in the semiotic perspective of Habib Ja'far Charles Pierce. The purpose of this study is to analyze semiotics in Habib Ja'far's Youtube content on interreligious dialogue. This research is qualitative and employs digital technology. The approach used in this study is Charles Sanders Peirce's semiotic theory as a benchmark in analyzing, where the theory uses triadic and can also rely more on trichotomy in understanding and analyzing problems, as for this research as follows: representation (sign), object, and interpretant (interpretation). The focus of this research is on representations with objects, where icons, symbols, and indexes are used as material for analysis to explore transformative tolerance education in interreligious dialogue content on Habib Ja'far's YouTube Channel under the name Jeda Nulis. Interreligious dialogue, which is a two-way conversation between religious leaders, reflects mutual respect, openness, knowing and understanding the values of each other's religions, and seeking common ground in diversity. Through interreligious dialogue, it becomes a mirror of the beauty of harmony in diversity.